Doughnut economics: seven ways to think like a 21st-century economist - Raworth, Kate (Vermont, 2017)
"Economics is broken. It has failed to predict, let alone prevent, financial crises that have shaken the foundations of our societies. Its outdated theories have permitted a world in which extreme poverty persists while the wealth of the super-rich grows year on year. And its blind spots have led to policies that are degrading the living world on a scale that threatens all of our futures.